2003
DOI: 10.1021/ja037272x
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Bis-π-allylpalladium Complex Catalyzed Asymmetric Allylation of Imines:  Enhancement of the Enantioselectivity and Chemical Yield in the Presence of Water

Abstract: The chiral pi-allylpalladium complex 2a, prepared from exoethylidenenorpinane 7, catalyzed the allylation of diverse imines with allyltributylstannane in the presence of 1 equiv of water in good to high enantioselectivities. The catalyst prepared from a 1:1 mixture of (E)- and (Z)-7 was found to be consisting of two stereoisomers 2a and 2b in 1.3:1 ratio. On separation, 2a catalyzed the allylation of imines in much higher enantioselectivities than 2b, giving the same major enantiomer and thereby justifying the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 135 publications
(50 citation statements)
references
References 17 publications
0
48
0
2
Order By: Relevance
“…Tatsächlich führte die Reaktion eines Phenylboronsäureesters mit 2-Cyclopentenon zu [90] Der Katalysezyklus wurde durch Kinetikstudien abgesichert und ist in Schema 74 dargestellt. [91] In [102][103][104] 6.1. Phosphanyl-Olefin-Liganden…”
Section: Shirakawa Hayashi Et Al Berichteten In Einem Nächstenunclassified
“…Tatsächlich führte die Reaktion eines Phenylboronsäureesters mit 2-Cyclopentenon zu [90] Der Katalysezyklus wurde durch Kinetikstudien abgesichert und ist in Schema 74 dargestellt. [91] In [102][103][104] 6.1. Phosphanyl-Olefin-Liganden…”
Section: Shirakawa Hayashi Et Al Berichteten In Einem Nächstenunclassified
“…Catalytic asymmetric allylation of imines has been achieved using the chiral π-allylpalladium chloride dimer as a source of the palladium catalyst [43]. More recently, it has been reported that in the presence of water the chemical yields and enantioselectivities of catalytic asymmetric allylations of imines were enhanced, the latter up to 91% ee [44]. Not only allylstannanes but also allylsilanes can be used as a nucleophilic allyl source (Scheme 1.38) [45], and in the presence of a chiral palladium catalyst the asymmetric allylation takes place smoothly giving high yields and high ee values.…”
Section: Nucleophilic Reactionsmentioning
confidence: 99%
“…[13][14][15][16][17][18][19][22][23][24][25] In order to study the involvement of the palladium catalyses in the allylation step of the above reaction (Scheme 1), we reacted allylboronate 11 with nitrobenzaldehyde 3a and imine 4 under the usual reaction conditions but in the absence of palladium catalyst (Scheme 7). The reaction of 3a with 11 gave smoothly 5a, clearly showing that the allylation of the aldehyde compo-Scheme 6.…”
Section: Mechanistic Considerationsmentioning
confidence: 99%